Analisis Kerajinan Boneka Dari Limbah Karung Goni Dan Kain PercaDitinjau DariGesture - Nia Lolo Sabrina Nasution; Sri Wiratma (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
This study aims to describe the cues on dolls made of jute sack waste and patchwork as crafts. The data study techniques in this study were observation, documentation and interviews. The total population of the study was 15 dolls in the doll craftsmen. The sampling technique of this researcher was total sampling, which was taken from the total population who drew doll crafts from gunny sacks and patchwork. The results showed that there was limited variation in facial expressions in doll products. Gestures on dolls are neat and sturdy but have elastic properties so that the movements of the dolls show character in the activity. In addition to the unique shape and color produced from the patchwork, it is a center point or a great attraction to attract consumers' attention. Furthermore, in making dolls from jute sack waste and patchwork, it is unique in its creation which is used as a reference for making a doll product, which has certain characteristics, for example the results of this doll have characteristics related to human activity.